2019
DOI: 10.1108/jhti-07-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship marketing and customer satisfaction in the Ghanaian hospitality industry

Abstract: Purpose The purpose of this paper is to investigate how relationship marketing practice can lead to customer satisfaction in the current practices in the hotel industry in Ghana. Globally, the hospitality industry ranks as one of the most competitive business sectors with competing organisations relying on a cocktail of strategies such as relationship marketing to stay relevant, and attract and retain customers. This paper examines how relationship marketing impacts on trust, commitment and satisfaction for cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…As the trust of corporate segment customers in their main banks increases, so does the customer satisfaction regarding the service they receive from their main banks. This result is similar to Amoako et al (2019) 's studies.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As the trust of corporate segment customers in their main banks increases, so does the customer satisfaction regarding the service they receive from their main banks. This result is similar to Amoako et al (2019) 's studies.…”
Section: Resultssupporting
confidence: 93%
“…Trust is an important factor that also affects customer satisfaction, because the business must first gain the customer's trust in order to create customer satisfaction (Amoako, Kutu-Adu, Caesar & Neequaye, 2019). A customer will only be able to reach the point of satisfaction if s/he has trust (Chaudhuri & Holbrook, 2001).…”
Section: Trustmentioning
confidence: 99%
“…In the field of tourism, Wu et al (2016) found that trust is an important predictor of patient satisfaction in medical tourism. Amoako et al (2019) also showed that customer satisfaction is influenced by trust and commitment in the hospitality industry.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Considerable academic debate about the relationship between trust and satisfaction exists. Although some studies ( Al-Ansi and Han, 2019 ; Melian-Alzola and Martin-Santana, 2020 ) showed that customer satisfaction has a positive effect on trust, others showed that customers’ positive perception of trust affects their satisfaction ( Chang, 2014 ; Wu et al, 2016 ; Amoako et al, 2019 ). In the field of tourism, Wu et al (2016) found that trust is an important predictor of patient satisfaction in medical tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, attention has been given to the implementation of food safety practices in most nations across the globe. e greatest impact of foodborne diseases has been reported in Africa [5]. In Ghana it is estimated that at least 1 out of 40 people are affected with foodborne diseases, which costs government 69 million dollars annually [6].…”
Section: Introductionmentioning
confidence: 99%